EKSPLANASI INKLUSIFITAS BAHASA DAN BUDAYA INDONESIA DALAM WACANA JURNALISTIK - Nur Fajar Arief (LITERA, 2010)
In general this research studies the phenomena of the exlpanations of Indonesian culture in news journalistic discourses (NJD) using the Indonesian language. The main research problem dealt with is, “How is Indonesian culture, which covers characteristics of cultural values, cultural perceptions, and cultural orientations, reflected in news journalistic discourses using the Indonesian language?” This research was systematized by using the qualitative approach. It belongs to interpretive discourse analysis. The methods include (1) text ethnography, (2)phenomenology, and (3) cultural-hermeneutics. The analytical stages utilize the principals and techniques of data analysis found in descriptive discourse analysis and critical discourse analysis. The data are texts on NJD, which are in the forms of words, sentences, and paragraphs with their macro-aspects, superstructure, andmicro-aspects. The sources of the data are nationally printed and regionally printed mass media (Kompas and Jawa Pos respectively). Research findings of the study are reported as follows. The characteristics of Indonesian cultural values reflectedin the macro-aspect included subaspects of thematization and thematic structure ofNJD. The perceptions of Indonesian culture reflected in the superstructure aspect included subaspects of contextualization pattern and realization of NJD. Moreover,the orientations of Indonesian culture as reflected in the micro-aspect included subaspect of meaning representation patterns, lexicalization, grammaticalization, and rhetoric of NJD.182